2004
DOI: 10.1017/s1461145703004012
|View full text |Cite
|
Sign up to set email alerts
|

Revising polypharmacy to a single antipsychotic regimen for patients with chronic schizophrenia

Abstract: Antipsychotic polypharmacy has been empirically used and a recent trend in favour of that mode of therapy has been suggested for the treatment of schizophrenia. The clinical efficacy, however, still remains to be clarified. In order to critically evaluate the usefulness of such kind of psychopharmacotherapy, antipsychotic combination regimen (polypharmacy) was switched to a treatment with the single main antipsychotic (monotherapy) in cross-tapered fashion, while approximately maintaining the total amount, for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
0
7

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(56 citation statements)
references
References 30 publications
1
48
0
7
Order By: Relevance
“…31 Individuals were often taking three antipsychotic medications and had been doing so for more than 6 months. Of the 44 patients included in the study, 22 (50%) were successfully converted to monotherapy without detriment to their mental health.…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Individuals were often taking three antipsychotic medications and had been doing so for more than 6 months. Of the 44 patients included in the study, 22 (50%) were successfully converted to monotherapy without detriment to their mental health.…”
Section: Managementmentioning
confidence: 99%
“…The authors concluded that most cases of multiple antipsychotic use were avoidable and recommended that polypharmacy 'should not be overused and should be the exception, to be used when other therapeutic options have failed'. 31 Suzuki et al also studied patients receiving high-dose antipsychotic polypharmacy without improvement in their symptoms who were switched to second-generation (atypical) antipsychotic monotherapy. 32 Of the 25 individuals recruited into the study, 23 were successfully switched to monotherapy with no detriment to their mental health at the end-point of the study (12 weeks after completion of their switch) and the vast majority showed an improvement in their Global Assessment of Functioning score.…”
Section: Managementmentioning
confidence: 99%
“…Of the 22 patients on monotherapy, 8 showed symptomatic improvement, whereas symptom levels for the other 14 were unchanged. 80 Dissemination of treatment algorithms alone has not been found to be effective, 16 but Chong et al reported that combining treatment algorithm implementation with periodic audits of algorithm compliance significantly decreased antipsychotic polypharmacy. 19 Thompson et al achieved a modest reduction using a multifaceted approach combining group education, academic detailing, and chart reminders.…”
Section: Discussionmentioning
confidence: 99%
“…the use of clozapine proved to be more effective than switching to another SGA in patients who have previously not responded to another SGA. 4) Polypharmacy with SGA Polypharmacy in schizophrenia is widespread all over the world 41 despite the fact that there is no evidence of the superiority of this empiricist therapeutic habit over monotherapy. Some consider that combinations of SGA are well tolerated and may be effective for the treatment of RS, while other authors remain more cautious due a lack of well-controlled studies 42 or evidence of harm as, for example, increased mortality.…”
mentioning
confidence: 99%
“…Some consider that combinations of SGA are well tolerated and may be effective for the treatment of RS, while other authors remain more cautious due a lack of well-controlled studies 42 or evidence of harm as, for example, increased mortality. 43 In a naturalistic study in seven psychiatric hospitals, Janssen et al 44 found that patients discharged with more than one antipsychotic had significantly poorer outcomes with respect to both mental state and social functioning, while Suzuki et al 41 observed an improvement when patients under antipsychotic polytherapy were switched to monotherapy. 5) Clozapine polypharmacy An incomplete response to clozapine is the persistence of psychotic symptoms despite a trial of clozapine with adequate doses (i.e.…”
mentioning
confidence: 99%